Pancreatic stellate cells reorganize matrix components and lead pancreatic cancer invasion via the function of Endo180. (1st January 2018) - Koikawa, Kazuhiro; Ohuchida, Kenoki; Takesue, Shin; Ando, Yohei; Kibe, Shin; Nakayama, Hiromichi; Endo, Sho; Abe, Toshiya; Okumura, Takashi; Horioka, Kohei; Sada, Masafumi; Iwamoto, Chika; et al.
Abstract: Specific cell populations leading the local invasion of cancer are called "leading cells". However, the underlying mechanisms are unclear. Here, we identified leading cells in pancreatic cancer and determined how these cells lead and promote cancer cell invasion in the extracellular matrix (ECM). Using three-dimensional matrix remodeling assay, we found that pancreatic stellate cells (PSCs) frequently invaded the collagen matrix with pancreatic cancer cells (PCCs), which invaded behind the invading PSCs. In addition, invading PSCs changed the alignment of collagen fibers, resulting in ECM remodeling and an increase in the parallel fibers along the direction of invading PSCs. Endo180 expression was higher in PSCs than in PCCs, Endo180 knockdown in PSCs attenuated the invasive abilities of PSCs and co-cultured PCCs, and decreased the expression level of phosphorylated myosin light chain 2 (MLC2). In mouse models, Endo180-knockdown PSCs suppressed tumor growth and changes in collagen fiber orientation in co-transplantation with PCCs. Our findings suggest that PSCs lead the local invasion of PCCs by physically remodeling the ECM, possibly via the function of Endo180, which reconstructs the actin cell skeleton by phosphorylation of MLC2. Highlights: Pancreatic stellate cells (PSCs) lead pancreatic cancer cells (PCCs) invasion by extracellular matrix (ECM) remodeling. Endo180 is related with invasive ability of leading PSCs via phosphorylation of myosin light chain 2 (MLC2). Inhibition of Endo180 in PSCs suppressed the ability of ECM remodeling and consequently suppressed co-cultured PCCs invasion.